2015
DOI: 10.1108/ijse-09-2013-0198
|View full text |Cite
|
Sign up to set email alerts
|

What drives behavioral intention of mobile money adoption? The case of ancient susu saving operations in Ghana

Abstract: Purpose – The purpose of this paper is to provide insights into the ancient susu savings operation in Ghana and the behavioural intention or willingness of susu collectors and users to adopt a mobile money (MM) platform as part of their savings practices. More specifically, this study investigates factors that determine one’s intention to adopt the MM space as a savings channel, particularly in place of more traditional ways of saving among many people in West Africa. Design/methodology/approach – Using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 25 publications
(27 reference statements)
1
40
1
2
Order By: Relevance
“…Grounded on Venkatesh et al () recommendations, this study adapted measurement items from related studies of UTAUT model. In measuring MMS adoption for trade dimensions such as user behaviour, this study profoundly adapted constructs from UTAUT model and related studies of mobile money adoption as well as from gaps identified from literature review (Osei‐Assibey, ). Since Venkatesh's instrument was valid and acceptable measure for the adoption model construct, it was adopted for this research.…”
Section: Methodsologymentioning
confidence: 99%
“…Grounded on Venkatesh et al () recommendations, this study adapted measurement items from related studies of UTAUT model. In measuring MMS adoption for trade dimensions such as user behaviour, this study profoundly adapted constructs from UTAUT model and related studies of mobile money adoption as well as from gaps identified from literature review (Osei‐Assibey, ). Since Venkatesh's instrument was valid and acceptable measure for the adoption model construct, it was adopted for this research.…”
Section: Methodsologymentioning
confidence: 99%
“…In addition, extra expenses that are incurred when migrating from desktop applications to m‐commerce can discourage an organisation or an individual from readily adopting mobile technology (Van der Boor et al, ). In most developing countries, there is a lack of legal and regulatory framework that governs the use of m‐commerce transactions (Osei‐Assibey, ). All the aforementioned barriers still need to be considered if the intention of the user to embrace the m‐commerce is to be effectively accomplished.…”
Section: Findings In the Selected Studies: Impact And Adoption Factormentioning
confidence: 99%
“…Thus, there is a need for research to investigate pathways through which mobile money can be deployed to improve financial inclusion. Second, majority of extant mobile money studies (e.g., Lashitew et al, 2019;Narteh et al, 2017;Osei-Assibey, 2015) have predominantly adopted quantitative methods such as regression analysis, limiting a configural understanding of conditions required to improve financial inclusion. As echoed by Veríssimo (2016) and Fiss (2007), the use of traditional quantitative methods like regression result in often treating factors individually with the effects of their combination arguably ignored.…”
Section: Introductionmentioning
confidence: 99%